Emphysema is associated with thoracic vertebral bone attenuation on chest CT scan in HIV-infected individuals. - Alycia Petraglia; Joseph K Leader; Matthew Gingo; Meghan Fitzpatrick; John Ries; Cathy Kessinger; Lorrie Lucht; Danielle Camp; Alison Morris; Jessica Bon (PLoS ONE)
Background Age-related chronic diseases are prevalent in HIV-infected persons in the antiretroviral therapy (ART) era. Bone mineral density (BMD) loss and emphysema have separately been shown to occur at a younger age and with lesser risk exposure in HIV-infected compared to HIV-uninfected individuals. In non-HIV infected smokers, emphysema has been shown to independently predict low BMD. We hypothesized that emphysema would independently associate with thoracic vertebral bone attenuation, a surrogate for bone mineral density, in HIV-infected individuals. Methods Clinical, pulmonary function, and radiographic data were analyzed for 164 individuals from the University of Pittsburgh's HIV Lung Research Center cohort. Chest CT scans were used to quantify emphysema and compute Hounsfield Unit (HU) attenuation of the 4th, 7th, and 10th thoracic vertebrae. The association between mean HU attenuation values across the three vertebrae and radiographic emphysema, age, sex, body mass index (BMI), steroid use, viral load, CD4 count, and forced expiratory volume in the first second (FEV1) was assessed by univariate and multivariate analyses. Results In univariate analysis, mean HU attenuation decreased with increasing age (p<0.001), pack years (p = 0.047), and percent emphysema (p<0.001). In a multivariable model, including pack years, age, sex, ART and steroid use, greater emphysema was independently associated with this surrogate marker of BMD in HIV-infected individuals (p = 0.034). Conclusions The association of emphysema with thoracic bone attenuation in HIV-infected individuals is consistent with previous reports in non-HIV infected smokers. These findings suggest that emphysema should be considered a potential marker of osteoporosis risk in HIV-infected individuals.